Reorientasi Politik Hukum Pengelolaan Wilayah Kelautan di Daerah Menurut Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah: Mendukung Visi Negara Maritim di Daerah - Sari Wiji Astuti (Jurnal Selat, 2015)
Archipelago are divided into provincial regions and these provincial regions shall be divided into districts and cities, as a unitary state is a consequence of the geographical condition of Indonesia’s maritime territory very wide, approximately 2 / 3 area of the country in the form of oceans. Indonesia was internationally recognized as the State Maritime defined in UNCLOS 1982 which authorizes and expands Indonesian waters with all the provisions that follow. Law politics government now trying to restore the paradigm of the development with a vision of strengthening maritime country, but Article 27 of Law No. 23 Year 2014 on Regional Government requires management of marine areas no longer in the blood of an autonomous government but the provincial government. what the purpose of Article 27 of Law No. 23 of 2014 and whether the politics of law Article 27 of Law No. 23 of 2014 in the management of marine areas in the region in accordance with national law politics? especially in realizing the vision of a maritime nation. The authority of the management of marine areas in the region has shifted from the authority of the government district / city under the authority of the provincial government as a result of the symptoms of centralization of Law No. 23 of 2014, when examined this case is contrary to the principle of local autonomy, so that needs to be re-examined legal political government to rebuild vision Indonesia as a pluralistic character of the State Maritime for society as a main pillar to build a maritime country has been made uniform in Law No. 23 of 2014. Key words : Marine Management, Legal Politics Maritime Country, Centralization of Law No. 23 Year 2014